DESIGNING A DIGITAL TEXTBOOK OF LANGUAGE ASSESSMENT AND EVALUATION ON FACILITATING FLEXIBLE LEARNING FOR UNDERGRADUATE STUDENTS - Nurma Dianti Putri; Nur Aisyah Zulkifli (Datokarama English Education Journal, 2024)
The purpose of this project is to identify the digital textbook that students need in language assessment and evaluation courses require, and to create that textbook using fliphtml5. This study employed the addie model as part of its research and development (r&d) methodology. A questionnaire, document list, and validation sheet are the methods used to collect the data. The department of English education of UIN Sultan Syarif Kasim Riau held this study on July 10, 2024. UIN Sultan Syarif Kasim Riau was the study's location. Participants in this study included lecturers and sixth-semester eed students. Data was also sent to learning material experts and media experts for validation in addition to need analysis. The study's findings demonstrate the need for digital textbooks as a tool in the teaching and learning process for both lecturers and students. The digital textbook, however, was based on a syllabus that appropriate with the higher curriculum. Additionally, the average calculation results (average measure) yielded a value of 0.620 with a moderate category, while the ICC reliability results (individual value, single measure) obtained an individual value of 0.450 or included in the poor category.